The econometrics of financial markets - Campbell, John Y. 1958-; Lo, Andrew W. 1960-; MacKinlay, Archie Craig 1955- (Princeton Univ. Press, 1997)
Each chapter develops statistical techniques within the context of a particular financial application. This exciting new text contains a unique and accessible combination of theory and practice, bringing state-of-the-art statistical techniques to the forefront of financial applications. Each chapter also includes a discussion of recent empirical evidence, for example, the rejection of the random walk hypothesis, as well as problems designed to help readers incorporate what they have read into their own applications
Erg. bildet: A solution manual to the econometrics of financial markets
Keywords: Econometrische modellen; Kapitaalmarkt; Marché financier - Modèles économétriques; Portfolio-analyse; Ökonometrisches Modell; Capital market -- Econometric models; Ökonometrie; Kreditmarkt